Entubulation techniques in peripheral nerve repair - Babu, Pauline; Behl, Anil; Chakravarty, B; Bhandari, PS; Bhatti, TS; Maurya, Sanjay (Indian Journal of Neurotrauma, 2008)
Peripheral nerve injuries are common, and there is no easily available formula for successful treatment. Although primary neurorrhaphy and nerve autografts are the most effective methods of repair, several newer options are at our disposal today. Though one can help speed up the nerve regeneration process to some extent, success is hindered by additional issues such as number of coaptation sites, supply of donor nerves and the limitations of nerve substitutes. There is now considerable evidence that peripheral nerves have the potential to regenerate if an appropriate microenvironment is provided. A better understanding of the biological processes involved in nerve regeneration process and the realization that nerve grafts serve as a guide for the growing neurons led to the concept of entubulation techniques. For distances of less than 3 cms, either a nerve conduit or an autologous vein graft serves equally well as nerve graft. Seeding the conduits with cultured Schwann cells has pushed the limit of nerve regeneration through a 6 cm gap. In experimental studies with Schwann cell lined bioengineered conduits gaps as large as 8cms can be bridged. Advances in bioengineering has allowed creation of composite neural tubes lined with Schwann cells and neurotropic agents that enhances regeneration of nerve fibers, block the invasion of scar tissue and autodegrade when it is no longer required. The evolution of the concept of entubulation, the early experimentation, the present development and various types of conduits are discussed here.
Keywords: nerve gap; nerve conduits; entubulation